Financial Aspect Analysis in Business Feasibility Studies - Nur Hidayah Pulungan; Dwi April Yani Simangungsong; Roza Hayadi; Suhairi Suhairi (Penerbit Jurnal Indonesia, 2022)
This article contains about what financial aspects have an effect on business viability. Which as we know that the Financial Aspect is one aspect that is very very important in the running of the business that will be run by the businessman. And in this paper the author will examine what financial aspects need to be considered and analyzed in order to study the feasibility of the business for the development of the business.